Morphological control of calcium carbonate crystallized in reverse micelle system with anionic surfactants SDS and AOT - Kang, Sung Hoon; Hirasawa, Izumi; Kim, Woo-Sik; Choi, Chang Kyun (Journal of colloid and interface science, 2005)
The influence of a surfactant over water on the polymorphism and crystal size of calcium carbonate produced by reaction crystallization in microemulsion systems was investigated in a mixing tank reactor. The crystallization was induced by the reaction between two aqueous micelle solutions (Na 2CO 3–CaCl 2) stabilized by anionic surfactants, SDS (sodium dodecyl sulfate) or AOT (sodium bis(2-ethylhexyl) sulfosuccinate). With increasing surfactant ratio to water, the water-in-oil microemulsion was stably developed and the morphology of the calcium carbonate crystallized in the micelles sharply transformed from calcite to vaterite. The influence of SDS on the polymorphism and crystal size of calcium carbonate was much clearer than that of AOT. In addition, with AOT, certain step changes in the morphology and crystal size occurred around a surfactant ratio to water ( R = [ H 2 O ] / [ surfactant ] ) of 15 due to a two-phase separation of the microemulsion.